Fenomena Penggunaan Media Sosial dan Pentingnya Pendidikan Etika Kristen di Era Disrupsi - Adi Saingo, Yakobus (Publisher STPKat, 2024)
Social media is used freely and without control causing quite a number of people in the era of disruption to engage in various actions that are not in accordance with religious norms and values. Therefore serious treatment is needed, one of which is Christian ethics education. The purpose of this study is to find out the phenomenon of social media use in the era of disruption and the importance of Christian ethics education. The research method used was literature review and analyzed using a descriptive approach. The results of the study explain that in facing the progress of the times, every Christian needs to understand the phenomenon of the use of social media in the era of disruption by most people, including: Spending a lot of time playing social media, social media as one of the perpetrators of crime, social media is one of the factors growing anti-social behavior. Apart from that, to prepare Christians to have a life that pleases God, it is necessary to take various approaches, including by implementing Christian ethics education in their daily lives, which aims to: Prepare Christians to face challenges of faith in the era of disruption, make them aware of the importance of social values, anticipate in the misuse of social media technology, as a means of instilling Biblical values, motivating to always be a blessing through social media in an era of disruption.